Performance Evaluation of Guava (Psidium guajava L.) Introductions in Arid Conditions of Western Rajasthan - Singh, Akath; Kumar, Suresh; Kulloli, R N (Annals of Arid Zone, 2016)
The growth, yield and quality traits of seven varieties of guava (Psidium guajava L.) were evaluated during the winter season of 2015-16. Plant height was higher in red fleshed and L-49 but plant spread and stem diameter was higher in Allahabad Safeda and Sarbati. The highest yield was recorded in Allahabad Safeda followed by L-49. Flesh color was pink in Lalit, red in Red Fleshed whereas white in other varieties. The fruit weight ranged from 87.2 g to 152.0 g in Lalit and Sarbati, respectively. Fruit size and number of seeds/100 g fruit was maximum in Sarbati whereas, pulp thickness was maximum in Allahabad Safeda. The highest TSS was observed in MPUAT Sel. 1 whereas, acidity was highest in Lalit. Total sugar was highest in Red Fleshed but the pectin content was observed highest in L-49.